INVASIVE RESPIRATORY ASPERGILLOSIS IS A TREATABLE DISEASE WITH EARLY DIAGNOSIS AND AGGRESSIVE THERAPY - (:unkn) unknown (INFORMA HEALTHCARE, 2010)
This study aimed to document outcome of invasive respiratory aspergillosis (IRA) in pediatric malignancy patients. Patients with febrile neutropenia episodes followed between January 2003 and May 2007 were enrolled. Antifungal therapy was added to those who were still febrile on the 5th day of febrile neutropenia treatment. Patients were screened with computerized tomographies. IRA was identified in 22 of 98 patients. There were 13 males and the mean age was 97 months. Proven infection was established in 3, probable in 7, and possible in 12 patients. Liposomal amphotericin B was administered to all patients and was successful in 10 patients. Modifications with caspofungin or voriconazole were done in liposomal amphotericin B failures. The median duration of antifungal therapy was 5.5 months. The median follow-up time was 29 months. There was no evidence of IRA in 12 patients after completion of cancer chemotherapy. Six patients died due to underlying disease, whereas IRA was either in remission or stable disease. Four patients were lost due to IRA. The remission rate for IRA was 82%. Survival at 37 months was 55% (95% confidence interval 25-47 months). The amount of time that absolute neutrophil count after initiation of treatment for IRA remained at zero was found to be an independent prognostic factor on survival (P = .01). These results suggest that early diagnosis and aggressive treatment may increase the successful outcome of IRA.
Keywords: aspergillosis; malignancy; pediatric; LIPOSOMAL AMPHOTERICIN-B; FUNGAL-INFECTIONS; PULMONARY ASPERGILLOSIS; NEUTROPENIC PATIENTS; HEMATOLOGICAL PATIENTS; SINGLE-INSTITUTION; CHILDREN; CANCER; CASPOFUNGIN; EFFICACY